Rare Concurrent Ileoileal and Ileocolic Intussusceptions in a Child Presenting With Painless Hematochezia - Jr-Rung Shiu; Hsun-Chin Chao; Cheng-Chan Chen; Chao-Yun Chi (Elsevier, 2010)
Double-site intussusceptions are very rare in children, and only a few have been reported. Here, we report a 17-month-old boy with double intussusceptions, whose clinical manifestations were painless hematochezia and anemia. Ultrasonography demonstrated an edematous, dilated bowel and two target lesions, suggesting multiple sites of intussusception. At surgery, intussusceptions were found in the ileoileal and ileocolic segments of the intestine. The cecum and proximal ascending colon were resected because of a gangrenous ileocolic intussusception. The ileoileal intussusception was reduced manually. Postoperatively, the patient was stable with no subsequent intestinal obstruction or hemorrhage.